2008
DOI: 10.1371/journal.ppat.1000075
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Transmission of BASE Induces Clinical Dullness and Amyotrophic Changes

Abstract: The disease phenotype of bovine spongiform encephalopathy (BSE) and the molecular/ biological properties of its prion strain, including the host range and the characteristics of BSE-related disorders, have been extensively studied since its discovery in 1986. In recent years, systematic testing of the brains of cattle coming to slaughter resulted in the identification of at least two atypical forms of BSE. These emerging disorders are characterized by novel conformers of the bovine pathological prion protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
95
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 26 publications
11
95
4
2
Order By: Relevance
“…Although atrophy of both type I and II muscle fibers had been detected in BASE cases in previous experiments, 8 evident changes were not detected in the skeletal muscle of the cases examined in this study. This discrepancy may have been due to the fiber-type grouping used in the previous studies, which had resulted in neurogenic atrophy of the innervated muscles, indicating that the muscular lesions in the BASE cases might not be associated with a neurogenic disorder.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Although atrophy of both type I and II muscle fibers had been detected in BASE cases in previous experiments, 8 evident changes were not detected in the skeletal muscle of the cases examined in this study. This discrepancy may have been due to the fiber-type grouping used in the previous studies, which had resulted in neurogenic atrophy of the innervated muscles, indicating that the muscular lesions in the BASE cases might not be associated with a neurogenic disorder.…”
contrasting
confidence: 68%
“…5 Additional studies have demonstrated that the BSE/ JP24 isolate can be transmitted to cattle 6 and that BSE/JP 24 and BASE have nearly the same incubation period during the first passage in Holstein cattle. 6,8 Research has also suggested that during subsequent passages, the incubation period of the disease may be shorter or more stable than that of the first passage and that its characterization may vary. The primary objective of this study was to further investigate the characteristics of the second passage of the disease by clinicopathologic analysis of BSE/JP24-infected cattle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…End point titration of the homogenate pool in RIII mice gave a titer of 10 3.5 mouse intracerebral and intraperitoneal ID 50 (median infective dose) units per gram of tissue and murine strain-type characteristics consistent with BSE-C. At 3 to 4 months of age, 30 calves were orally dosed with 100 g of the pooled brainstems, applied by syringe to the base of the tongue at the entrance to the pharynx. 35 Ten calves received no treatment and served as controls. Clinical monitoring of cattle was maintained throughout the study.…”
Section: Source Animals and Inoculummentioning
confidence: 99%
“…Atypical BSEs are classified into 2 forms on the basis of the molecular weight of the proteinase K-resistant core fragment of the abnormal prion protein PrP Sc : L-type BSE (L-BSE) or bovine amyloidotic spongiform encephalopathy and H-type BSE (H-BSE) [3,5]. Several studies have indicated that L-BSE and H-BSE are caused by different prions with varying biological characteristics [4,11,12]. A limited number of atypical BSE cases have been reported, and sporadic occurrence may be supposed as their origin [2].…”
mentioning
confidence: 99%